2012
DOI: 10.4236/ojap.2012.13008
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Atmospheric Conditions on Influenza in Southern China. Part I. Taking Shenzhen City for Example

Abstract: In this study, we analyse the relationship between the occurrences of influenza in Shenzhen, a rapid developing city in subtropic regions of southern China with over 10 million populations, and the vapor pressure (VP), the concentrations of atmospheric pollutants (SO 2 , NO 2 , PM 10 ) for the period of 2003-2008. Using the data such as the rate of Influenza-Like-Illness (ILI (%)), the concentrations of pollutants and vapor pressure, we show quite different results from previous research conducted in other re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The results of cross wavelet analysis and GAM indicated there was a positive relationship between SO 2 and ILI cases, which was in accordance with the results of Hwang et al [34], but different from some previous studies [23, 32]. Some studies have found that the cause of the negative association between SO 2 and ILI is that the acidic environment influences virus survival and decreases virus transmission [36, 37]. In contrast, an experimental study demonstrated that inhalation of SO 2 at 26 mg/m 3 after influenza virus infection can raise the risk of pneumonia in mice [38].…”
Section: Discussionsupporting
confidence: 63%
“…The results of cross wavelet analysis and GAM indicated there was a positive relationship between SO 2 and ILI cases, which was in accordance with the results of Hwang et al [34], but different from some previous studies [23, 32]. Some studies have found that the cause of the negative association between SO 2 and ILI is that the acidic environment influences virus survival and decreases virus transmission [36, 37]. In contrast, an experimental study demonstrated that inhalation of SO 2 at 26 mg/m 3 after influenza virus infection can raise the risk of pneumonia in mice [38].…”
Section: Discussionsupporting
confidence: 63%
“…Exposure to PM 2.5 can decrease the function of alveolar macrophages and pulmonary tracheal cilia, and raise the susceptibility of individuals to viruses 30 . PM 10 may reduce ultraviolet radiation reaching the ground and cause the spread of influenza virus infection 31 . We found that PM 2.5 and PM 10 were significantly associated with influenza.…”
Section: Conclusion and Discussionmentioning
confidence: 66%
“…30 PM 10 may reduce ultraviolet radiation reaching the ground and cause the spread of influenza virus infection. 31 We found that PM 2.5 and PM 10 were significantly associated with influenza. In our research, influenza virus was also correlated with NO 2 , which was consistent with the results of Huang in Nanjing.…”
Section: Influenza Virus Is a Common Pathogen Of Arti In Children Inmentioning
confidence: 60%
“…In our study, using ILI data over a 12-year period, we identified an annual seasonal pattern in Chongqing, with influenza activity peaking around December to January each winter, the significant seasonality and periodicity is consistent with the previous studies [ 9 , 10 ]. The seasonal characteristics of Chongqing are similar to those of Shenyang, but different from Shenzhen, whose ILI(%) peak occurs in summer [ 36 ]. In addition, to facilitate early warning, we added abnormal feedback over 95% forecast Confidence Intervals to forecast ILI trends and seasonality.…”
Section: Discussionmentioning
confidence: 99%